Pre-flight Functionality Check to Enhance Mission Efficacy of Precision Guided Munitions - Maini, A.; Verma, A. (Defense science journal, 2009)
Precision-guided munitions (PGMs), because of their precision strike capability, are used extensively in the modern warfare. The efficacy of the mission is critically dependent on the successful deployment of the weapon. To ensure high level of effectiveness of these sophisticated weapons, these must be tested at regular intervals. Periodic functionality checks of these weapons are carried out using comprehensive characterisation systems. In addition to comprehensive testing, pre-flight functionality checks with the weapon strapped on to the launch platform using portable test systems should be carried out. These functionality checks, also referred to as serviceability checks, perform Go/No Go testing of the weapon by focusing on one or two vital parameters of the guided weapon. Pre-flight functionality check of PGM allows a quick appraisal on the functional status of the vital operational parameters of relevance to efficacy of the mission. This review highlights the parameters that need to be checked, both for comprehensive testing of these weapons on a periodic basis and also those required for pre-flight functionality or readiness checks. International systems available for the purpose have also been reviewed, vis-à-vis, their capabilities and limitations to perform the two types of tests with particular emphasis on the pre-flight functionality checks with guided weapon in strap-on condition. Some alternative design approaches have also been proposed. Keywords: